Anti-ulcerogenic effect of osajin on indomethacin-induced gastric damage in rats - Koc, Murat; Erol, Huseyin Serkan; Çakir, Ahmet; Yildirim, Serkan; Halici, Mesut Bünyami (University of Veterinary and Pharmaceutical Sciences, 2020)
Ulcer is the most common undesirable result of using non-steroid anti-inflammatory drugs such as indomethacin. In the present study, osajin was experimentally used on indomethacin-induced gastric ulcer in rats. Osajin was purified from Maclura pomifera (Raf.) C. K. Schneid fruits by using the chromatographic methods. Thirty six rats were divided into six groups as follows: healthy (control), IND (indomethacin), RAN (ranitidine, 25 mg/kg), OSJ 100 (osajin, 100 mg/kg), OSJ 200 (200 mg/kg) and OSJ 400 (osajin, 400 mg/kg). Following a 24-h fasting, IND was administered to the treatment groups at a dose of 25 mg/kg. RAN and OSJ were given orally to rats following 5 min of IND administration. Then, gastric tissues were taken 6 h after the IND administration. Determination of the ulcer area, pathological evidence, and biochemical indices such as lipid peroxidation, superoxide dismutase, glutathione, and catalase were performed. IND generated diffuse ulcer areas, severe hyperaemia, oedema, necrotic epithelium, and mononuclear cell infiltration in the mucosa, and significantly increased lipid peroxidation while also decreasing the glutathione concentration, superoxide dismutase and catalase activities of the tissue. OSJ and RAN showed significant amelioration on ulcer area and biochemical indices. Therefore, OSJ may be potentially therapeutic for gastric ulcers.
Keywords: 3. Good health